Public Financial Institutions in Developed Countries-Organization and Oversight - Ratnovski, Lev (IMF Working Papers; Working Paper ;, 2007)
While public financial institutions (such as public development banks) are commonly associated with developing countries, in fact they are prevalent in the developed world as well. We study a sample of public financial institutions in industrialized countries and identify dominant trends in their organization and oversight. While practices in developed countries may be a useful reference point, a more nuanced approach, accounting for the disparity of institutional environment, regulatory capacity, and government accountability and effectiveness, may be required in developing countries. Further investment in the accumulation of evidence and formulation of best practices in the organization and oversight of public financial institutions seems warranted and necessary. This paper was prepared while Mr. Ratnovski was working in the Financial Supervision and Regulation Division during January-April 2006. The authors are grateful to Jonathan Fiechter, David Marston, and participants of an MCM seminar in April 2006 for their helpful comments.